Relationship of Eosinophils and Plasma Cells to Biofilm in Chronic Rhinosinusitis. Issue 4 (July 2013) - Arjomandi, Hamid; Gilde, Jason; Zhu, Sutao; Delaney, Sean; Hochstim, Christian; Mazhar, Kashif; Wrobel, Bozena; Markarian, Alexander; Masood, Rizwan; Rice, Dale
Background: This study investigates the relationship of eosinophils and plasma cells to biofilm in chronic rhinosinusitis (CRS). A prospective observational study was performed at the Keck Hospital, University of Southern California, Department of Otolaryngology, Los Angeles, CA. Methods: A total of 29 patients, 20 undergoing endoscopic sinus surgery for CRS and 9 control patients undergoing septoplasty for nasal obstruction without history or evidence of CRS, were included in this study. Contiguous sinonasal mucosa sample sections were examined by hematoxylin and eosin (H&E), fluorescence in situ hybridization (FISH), and immunohistochemistry (IHC) for biofilm, microbes, eosinophil major basic protein (EMBP), and cluster designation 27 (CD27). EMBP and CD27 were used as eosinophil and plasma cell markers, respectively. Results: Biofilm was visualized in 15 of 20 patients with CRS on H&E sections, confirmed by microbial presence using FISH. Biofilm was not identified in tissue samples of the nine control patients. On IHC analysis, CD27 and EMBP expression were significantly higher in patients with CRS compared with control (p < 0.05) and had greater expression in biofilm-positive patients compared with biofilm-negative patients. Nasal polyps correlated with higher expression of CD27 and EMBP, but in CRS patients without polyps CD27 and EMBP was also significantly greater in biofilm-positive specimens compared with biofilm-negative specimens. Conclusion: Biofilm presence in CRS appears to correlate to host inflammatory response involving plasma cell and eosinophil recruitment.